Inhibitory Effects of Rhaponticin on Osteoclast Formation and Resorption by Targeting RANKL-Induced NFATc1 and ROS Activity - He, Jianbo; Chen, Kai; Deng, Tiancheng; Xie, Jiewei; Zhong, Kunjing; Yuan, Jinbo; Wang, Ziyi; Xiao, Zhifeng; Gu, Ronghe; Chen, Delong; Li, Xiaojuan; Lin, Dingkun; et al. (Frontiers in Pharmacology, 2021)
The extravagant osteoclast formation and resorption is the main cause of osteoporosis. Inhibiting the hyperactive osteoclastic resorption is considered as an efficient treatment for osteoporosis. Rhaponticin (RH) is a small molecule that has been reported to possess anti-inflammatory, anti-allergic, anti-fibrotic, and anti-diabetic activities. However, the influence of RH on osteoclasts differentiation and function is still unclear. To this end, an array of assays including receptor activator of nuclear factor kappa-Β (NF‐κB) ligand (RANKL) induced osteoclastogenesis, tartrate-resistant acidic phosphatase (TRAcP) staining, immunofluorescence, and hydroxyapatite resorption assays were performed in this study. It was found that RH had significant anti-catabolic effects by inhibiting osteoclastogenesis and bone resorption without cytotoxicity. Mechanistically, the expression of NADPH oxidase 1 (Nox-1) was found to be suppressed and antioxidant enzymes including catalase, superoxide dismutase 2 (SOD2) and heme oxygenase-1(HO-1) were enhanced following RH treatment, suggesting RH exhibited antioxidant activity by reducing the generation of reactive oxygen species (ROS) as well as enhancing the depletion of ROS. In addition, MAPKs, NF‐κB and intracellular Ca2+ oscillation pathways were significantly inhibited by RH. These changes led to the deactivation of osteoclast master transcriptional factor-nuclear factor of activated T cells 1 (NFATc1), as examined by qPCR and Western blot assay, which led to the decreased expression of downstream integrin β3, c-Fos, cathepsin K and Atp6v0d2. These results suggested that RH could effectively suppress RANKL‐regulated osteoclast formation and bone resorption. Therefore, we propose that RH can represent a novel natural small molecule for the treatment of osteoporosis by inhibiting excessive osteoclast activity.